MARKET STUDY ON ROMANIAN AGRICULTURAL PRODUCTS IN THE CONTEXT OF ENSURING FOOD SECURITY AT THE NATIONAL LEVEL - Andreea-Daniela GIUCÄ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Food security has gained special attention from political representatives around the world, mainly due to the important role it plays in achieving the Sustainable Development Goals (SDGs). Considering that agricultural production contributes directly to ensuring food security, this study aimed to present an overview of the agricultural products market in Romania, in the context of ensuring food security. The study started from the analysis of statistical indicators regarding the average annual consumption per inhabitant, production per inhabitant and current prices for the main categories of agricultural products, provided by the National Institute of Statistics for the period 2018-2022. The presented indicators were processed by statistical methods, calculating: the average, the standard deviation, the coefficient of variation and the annual growth rate, and then analyzed for each category of agricultural products separately. The results showed that, an average annual consumption per inhabitant with a relatively constant dynamic for the categories of agricultural products analyzed. The category of agricultural products that recorded the highest consumption was milk and milk products in milk equivalent 3.5% fat (excluding butter). In terms of the production of the main agricultural products per capita, cereals for grains stood out by achieving the highest production per capita, followed by milk. Cereals value at producer price (including seeds) register the highest level.